Infundibulohypophysitis in a man presenting with diabetes insipidus and cavernous sinus involvement. Issue 6 (1st December 2001) - Tubridy, N; Saunders, D; Thom, M; Asa, S L; Powell, M; Plant, G T; Howard, R
Abstract : Infundibulohypophysitis is an unusual inflammatory condition that affects the infundibulum, the pituitary stalk, and the neurohypophysis and may be part of a range that includes lymphocytic hypophysitis. Lymphocytic hypophysitis occurs mainly in women and most often presents in the later stages of pregnancy. Infundibulohypophysitis usually presents with diabetes insipidus and the cause remains unclear. The case of a 46 year old man with a 12 week history of polyuria and polydipsia is reported. Cranial diabetes insipidus was diagnosed on the basis of a water deprivation test. Initial cranial and pituitary imaging studies were normal. He subsequently developed symptoms of panhypopituitism over a period of 6–9 months and then, more acutely, developed diplopia secondary to a fourth nerve palsy. Further brain imaging studies disclosed an enhancing pituitary stalk and a left cavernous sinus lesion. An initial trial of immunosuppressive treatment did not help symptoms significantly. The diagnosis of infundibulohypophysitis was made on histological evidence. The patient was treated with prednisolone and methotrexate. At 9 months he is well, without symptoms, and the radiological abnormalities have resolved.